The behaviours of lighweight foamed concrete beam with different size of square hollow section - Ahmad Fahimi, Zainal Abidin (2014)
Lightweight foamed concrete is one type of concrete that can be a replacement for conventional concrete which is widely used in construction industry nowadays. High density of conventional concrete makes structural elements heavier compare to the lightweight foamed concrete. Using lightweight foamed concrete as other alternatives to replace the conventional concrete will make the concrete more lighter and by addition of making a hollow section along the beam, it can reduce more weight of concrete itself. The main purposes of this study are to examine the behaviour of beam in term of flexural strength, deflection propagated and crack pattern. The size of beam used in this study is 1 5Ox200x3000mm. Four type of sample with different size of square hollow have been used. The sample A with no hollow, sample B with size 45x45rnjn of hollow size, sample C with size 60x6Omm of hollow size and sample D 7Ox7Omm of hollow size and it been placed along the length of beam. The density of lightweight foamed concrete was 1600kg/m3 with 1:2 of water cement ratio and 1:3 for water sand ratio. The testing that involved in this study is four point flexural tests. The result shows that the flexural strength of the samples reduced due to the different size of square hollow section. The flexural was reduced to 21.85% for Beam B, 22.01% for Beam C and 28.78% for Beam D respectively. Result for deflection shows that hollow beam was having more deflection compared to solid beam. As for deflection profile at a constant loading , Beam A, Beam B, Beam C and Beam D show the same profile but with different value of maximum deflection which is 8.96mm, 9.37mm, 10.14nim and 12.13mm. Cracking pattern result shows same behaviour which is crack at shear and in inclined pattern. First crack loading result for Beam A, Beam B, Beam C and Beam D was 16.2kN, 1 l.29kN, 10.24kN, and 8.72kN respectively.